Tren Penggunaan Media Pembelajaran Pada Jenjang Sekolah Dasar - Made Adi Nugraha Tristaningrat; Komang Trisna Mahartini (STAHN Mpu Kuturan Singaraja, 2023)
The purpose of this research is to re-examine the trend of employing learning media to enhance primary school learning outcomes. A meta-analysis strategy was employed in this study. In order to make the author's data collection process easier, this research starts by looking for pertinent themes. Searches in online publications using the terms Learning Media on Learning Outcomes of Elementary School Students produced the results. Ten articles from the years 2020–2022, which are still very relevant, are the only ones that can be found after a limited search. In order to support this paper, the data that has been collected is next examined. According to the analysis's findings, media use in the classroom has been shown to enhance student learning outcomes. Additionally, students' interactions with the media during the learning process vary. Through the usage of media during the learning process, it can also boost students' capacity to comprehend the subject matter readily.